Agrarian reform in Chile : an economic study - Swift, Jeannine (Lexington, Mass. : Heath Lexington Books, 1971)
The constraints of agrarian reform adopted by Chile in 1964
A revision of the author's thesis, Massachusetts Institute of Technology, 1969.
Includes bibliographical references: p. [115]-118.
obn23/01/2019
Loans
Keywords: Land reform; Agriculture